Cognitive impairment influencing factors in the middle-aged and elderly population in China: Evidence from a National Longitudinal Cohort Study - Biqi Zu; Ning Wang; LiJun Fan; Jinsong Huang; Yunan Zhang; Meiling Tang; Yulan Wu (PLoS ONE, 2025)
Objective The study aimed to explore the factors influencing cognitive impairment among middle-aged and elderly individuals in China, utilizing data from the China Health and Retirement Longitudinal Study (CHARLS). By examining the combined effects of socioeconomic factors, health behaviors, chronic diseases, and other multidimensional factors, this research seeks to provide evidence for the development of targeted public health policies and interventions. Methods This study utilized data from the 2018 wave of the CHARLS database, including a total of 19,307 participants aged 45 and older. Cognitive impairment was assessed using the Mini-Mental State Examination (MMSE), with thresholds adjusted for education levels. A combination of LASSO (Least Absolute Shrinkage and Selection Operator) regression and logistic regression models was employed to identify significant risk and protective factors for cognitive impairment. RCS (Restricted cubic splines) were used to explore the dose-response relationship between sleep duration and cognitive function. Results The analysis identified several significant risk factors for cognitive impairment, including age, urban household registration, self-rated health as fair, chronic disease, impaired instrumental activities of daily living (IADL), alcohol consumption and exercise. Protective factors included sleep duration, being female, divorced or widowed, self-rated health as poor and disability. The study also found that sleep duration followed a U-shaped relationship with cognitive function, with an optimal sleep duration of 5.83 hours per day. Conclusion This study highlights the multifactorial nature of cognitive impairment and underscores the importance of early interventions targeting modifiable risk factors such as chronic diseases and lifestyle behaviors. The findings contribute to the growing body of knowledge on cognitive impairment in China’s aging population and provide a basis for evidence-based public health strategies.